Maleri i Norge 1945-2000. - Eckhoff, Audun (Oslo : National Museum of Contemporary Art, 2001)
Ekeland, Arne ; Bergman, Anna-Eva ; Weidemann, Jakob ; Johs, Rian ; Ransve, Bjorn ; Heske, Marianne ; Torriset, Kjell ; Fyri, Dag ; Nielsen, John David ; Elstrom, Steinar ; Lorentzen, Ida ; Sorensen, Thorbjorn ; Kleiva, Per
Noors & Engels
Painting in Norway 1945 - 2000, National Museum of Contemporary Art, Oslo, 31.05 - 16.09.2001
boek
Keywords: Noorwegen